2020
DOI: 10.3390/ijerph17061910
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Active Living Environments and Mental Health: A Canadian Epidemiological Analysis

Abstract: Environments that promote use of active transport (walking, biking, and public transport use) are known as “active living environments” (ALE). Using a Canadian national sample, our aim was to determine if ALEs were associated with mental health outcomes, including depressive symptoms, and mood and anxiety disorders. Data from the Canadian Community Health Survey from 2015–2016 was used for demographic characteristics and mental health outcomes (n ≈ 110,000). This data was linked to datasets from the Canadian U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…While geospatial measures of population dependency have been widely related elsewhere to chronic physical health problems [36], we found few stable associations, likely reflecting age-specific patterns of mental service contacts. A recent Canadian study found no association between mental health outcomes and physical activity-friendliness of built environments [42]. A lack of statistical significance in certain hypothesized prediction patterns may be related to narrower between-neighbourhood sociodemographic differences within less-populated jurisdictions, e.g., small proportions of minority ethnic groups [25].…”
Section: Discussionmentioning
confidence: 97%
“…While geospatial measures of population dependency have been widely related elsewhere to chronic physical health problems [36], we found few stable associations, likely reflecting age-specific patterns of mental service contacts. A recent Canadian study found no association between mental health outcomes and physical activity-friendliness of built environments [42]. A lack of statistical significance in certain hypothesized prediction patterns may be related to narrower between-neighbourhood sociodemographic differences within less-populated jurisdictions, e.g., small proportions of minority ethnic groups [25].…”
Section: Discussionmentioning
confidence: 97%
“…Walking itself has been identified as Canadians’ leading activity to stay fit; it is inexpensive and generally possible for individuals of all ages 27. While growing evidence indicates that walking also has benefits to mental health and well-being, recent studies note that the research remains limited and incomplete for associations between individuals’ physical activity and their residential built environments with selected mental health outcomes 28 29. A small body of literature has found that adults with diabetes residing in poorer or more materially deprived neighbourhoods experience worse mental health outcomes compared with those residing in more affluent neighbourhoods 30 31.…”
Section: Introductionmentioning
confidence: 99%
“…We use multiple types of linked data from national survey, administrative and socioenvironmental sources, acquired through Statistics Canada’s Social Data Linkage Environment. Previous studies have used linked data to examine associations between individual-level and residential measures of active living with use of active transportation, self-reported mood and anxiety disorders, and premature cardiometabolic mortality 26 29 32. We aim to address the question: do adults 35 years and above with a pre-existing cardiometabolic condition residing in neighbourhoods that are less activity-supportive have higher risk of hospitalisation for mental health and substance use disorders, independently of their physical activity level?…”
Section: Introductionmentioning
confidence: 99%